The influence of humidity on the high voltage blocking reliability of power IGBT modules and means of protection. (September 2018) - Papadopoulos, Charalampos; Corvasce, Chiara; Kopta, Arnost; Schneider, Daniel; Pâques, Gontran; Rahimo, Munaf
Abstract: High voltage IGBT modules are used in high power applications including traction, industrial drives, grid systems and renewables such as in wind-power generation and conversion. Many of these applications are subject to harsh environmental conditions and in particular when the inverter cabinets do not shield the power electronics, including the IGBT modules, from such conditions. As an example, IGBT modules can be exposed to severe humidity levels. In this paper we investigate the influence of the combination of humidity and high voltage on the blocking reliability of 6.5 kV IGBT and diode devices. An improved testing approach High Voltage, High Humidity, High Temperature reverse biased (THBHV-DC) when compared to classical THB is applied to assess the robustness of different termination designs and passivation stacks. Full description of the failure mode and of its correlation to the humidity induced electrical field modifications is also provided. This analysis offers an insight on the design and testing aspects which are of key importance to the development of environmentally robust high power IGBTs. Highlights: Simulation prediction of potential failure points on 6.5kV IGBTs and Diodes shown simulating dry vs. wet conditions THBHV-DC or H3TRB test performed and el. results shown Optical analysis of failed devices shown Failure explained by simulations and theory by corrosion of passivation material Every point of corrosion theory proven on the device by SEM and EDX analysis (Nitride corrosion, Nitride outgassing, Aluminum corrosion, Polyimide lift-off) Improved devices shown with improved capability